Atomic resolution imaging and spectroscopy of single Barium atoms and functional groups on graphene oxide - Boothroyd, C. B.; Moreno, M. S.; Duchamp, M.; Kovács, A.; Monge, Natalia Eugenia; Morales, Gustavo Marcelo; Barbero, César Alfredo; Dunin Borkowski, R. E. (Elsevier Science, 2014)
Fil: Boothroyd, C. B.. Peter Grünberg Institute; Alemania